Assay and Characteristics of Circadian Rhythmicity in Liquid Cultures of Neurospora crassa - Perlman, Janine (1981)
Previous work on circadian rhythms of Neurospora crassa has been done almost exclusively with cultures expressing rhythmic conidiation and growing on solid agar medium. Such conditions severely restrict the kinds of biochemical experiments that can be carried out. We have now developed systems which allow indirect assay of circadian rhythmicity in liquid culture. Neurospora was grown in glucose and acetate liquid media under conditions which result in a range of growth rates and morphologies. Liquid media were inoculated with conidia and the cultures were grown in constant light for 33 or 48 hours, by which time floating mycelial pads had formed. Experimental pieces of mycelium then were cut and placed in fresh new liquid medium. As controls, other pieces of mycelium were cut and put directly on solid agar medium in race tubes. All cultures were transferred to constant darkness at this time. This light-to-dark transition set the phase of the circadian clock of both the liquid and solid cultures. At various times after the light-to-dark transition, the mycelial pieces in the liquid were transferred in the dark to solid medium in race tubes, where they grew normally and conidiated rhythmically. Comparison of the phase of the rhythm in these race tubes to the controls demonstrated that, under appropriate conditions, the circadian clock of the liquid cultures functions normally for at least two cycles in constant conditions. Using these culture systems, a significantly greater variety of biochemical studies of circadian rhythmicity in Neurospora is now possible.